The reception of Edmund Burke in Europe - Fitzpatrick, Martin, 1944-; Jones, Peter, 1935 December 18- (Athlone critical traditions series., 2017)
"Over the last fifty years the life and work of Edmund Burke (1729-1797) has received sustained scholarly attention and debate. The publication of the complete correspondence in ten volumes and the nine volume edition of Burke's Writings and Speeches have provided material for the scholarly reassessment of his life and works. Attention has focused in particular on locating his ideas in the history of eighteenth-century theory and practice and the contexts of late eighteenth-century conservative thought. This book broadens the focus to examine the many sided interest in Burke's ideas primarily in Europe, and most notably in politics and aesthetics. It draws on the work of leading international scholars to present new perspectives on the significance of Burke's ideas in European politics and culture."--